Promotion of Co-operation in Classification Research - Neelameghan, A. (Journal of Information and Knowledge, 2000)
Reviews the Indian Standard Glossary of classification terms (1964) and Parkhi’s Decimal classification and colon classification in perspective. Examines and establishes the value of a glossary of terms to facilitate communication among those interested in library classification. The development of the Indian Glossary is traced briefly. Attention is drawn to the structure of the Glossary and the advantages of the classified arrangement of the terms is stressed upon. Points for consideration in the revision of the Glossary are mentioned. Parkhi’s method of comparison of DG and CC on the basis of postulates and principles is commented upon and commended. Highlights the value of the books to classificationists, classifiers, and teachers and students of library science.